Ethics for the information age - Quinn, Michael J. (Boston, Massachusetts : Addision-Wesley Publishing Company, 2011)
In an era where information technology changes constantly, a thoughtful response to these rapid changes requires a basic understanding of IT history, an awareness of current issues, and a familiarity with ethics. Ethics for the Information Age is unique in its balanced coverage of ethical theories used to analyze problems encountered by computer professionals in today$1 (Bs environment. By presenting provocative issues such as social networking, government surveillance, and intellectual property from all points of view, this market-leading text challenges students to think critically and draw their own conclusions, which ultimately prepares them to become responsible, ethical users of future technologies.s
Catalysts for change -- Introduction to ethics -- Networked communications -- Intellectual property -- Privacy -- Computer and network security -- Computer reliability -- Professional ethics -- Work and wealth.
Includes bibliographical references and index.
Keywords: ELECTRONIC DATA PROCESSING -- MORAL AND ETHICAL ASPECTS